Lipidomics Reveals That Rice or Flour as a Single Source of Carbohydrates Cause Adverse Health Effects in Rats - Wang, Siyu; Wang, Wenjun; Mao, Hongmei; Zhu, Mingyu; Xu, Zihan; Wang, Jun; Zhang, Xuesong; Li, Baolong; Xiang, Xuesong; Wang, Zhu (Frontiers in Nutrition, 2022)
The type of diet is very important for the maintenance of health and nutrition. How does the sole source of carbohydrate from rice- or flour-based diet effect blood sugar has not been clearly answered for a long time. In order to explore the effects of these diets, sixty SD rats were randomly divided into three groups: control group (C group, AIN-93, standard diet), rice diet group (R group), and flour diet group (F group). All the rats were fed for 7 weeks in total by the assigned diets for 4 weeks (stage 1, S1) and all by AIN-93 diet for 3 weeks (stage 2, S2). The body weight of all the rats were monitored and serum samples were taken for testing blood glucose, biochemical indicators and untargeted lipidome. It was found that both rice and flour-based diets caused weight gain, but the flour diet had a significant increase in blood sugar and low-density lipoprotein (LDL), while a significant decrease in albumin (ALB) and triglycerides (TG). Twenty-three and 148 lipids were changed by lipidomics in rice diet group and flour diet group respectively, and two lipids showed the same changes in the two groups, which were all belong to TGs, namely TG(16:0/16:0/16:1) and TG(16:0/16:1/18:2). This shows that a single diet source has a significant effect on the health and nutrition in rats. Fortunately, we can recover this effect through the subsequent standard diet, allowing the rats to return to normal blood sugar, weight and biochemical indicators. A model can predict the diet types through logistic regression method. Finally, we proposed that is a single diet increases blood sugar and weight through a decrease in TGs, and blood sugar and weight return to normal after a standard diet. Taken together, the short-term negative effects caused by a single diet can be recovered by a standard diet and further proves the importance of diet types.